PRODUKTIVITAS RUMPUT LAUT DALAM SISTEM BUDIDAYA TRADISIONAL DAN MODERN: SEBUAH REVIEW - Andriani, Yuli; Pratama, Rusky I.; Aisyah, Aisyah (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
Seaweed productivity is an important factor in the success of cultivation, both in traditional and modern systems. This article reviews various seaweed cultivation methods applied in different regions, with a focus on comparing productivity between traditional and modern systems. This study examines the productivity of seaweed within the context of traditional and modern cultivation systems, aiming to provide a better understanding of the efficiency and sustainability of both approaches. Through an in-depth literature review, this research compares traditional methods, such as manual planting in shallow waters, with modern techniques like the use of floating rafts and automated systems. Results indicate that while traditional methods hold significant cultural and economic value, modern systems tend to offer higher productivity and lower environmental impact. However, challenges in adopting new technologies within coastal communities must be addressed to ensure a successful transition. These findings are expected to provide valuable insights for stakeholders in enhancing sustainable seaweed cultivation practices.